PROSES COLLABORATIVE GOVERNANCE DALAM PENANGANAN ORANG DENGAN GANGGUAN JIWA (ODGJ) PASCA REHABILITASI DI RSJ TAMPAN KOTA PEKANBARU TAHUN 2023 - Amara, Siti Khofifah; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the process of collaborative governance in managing people with mental disorders after rehabilitation at Tampan Mental Hospital, Pekanbaru City, in 2023. A qualitative descriptive method was applied, with data collected through interviews and documentation. The study focuses on the roles and interactions between Tampan Mental Hospital and the Riau Provincial Social Service, using Ansell and Gash’s collaborative governance process theory, which includes five indicators: face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. The findings indicate that collaboration between the two institutions has not been optimal due to unclear delegation of responsibility, lack of structured coordination, and limited post-rehabilitation support. Keywords: Collaborative Governance, People with Mental Disorders, Process, Rehabilitation